Kepedulian Pemuka Masyarakat Terhadap Warung Remang-Remang - zuwirda, zuwirda (Universitas Islam Negeri Imam Bonjol Padang, 2019)
In Jorong Lubuk Gadang there are two stalls that are in the spotlight for the community, both stalls only provide coffee and tea types, but now it has been added to liquor, karaoke and gambling gambling. Stalls are only available to add lighting (dimly lit). This condition if left unchecked will certainly disturb and influence the surrounding community, especially the younger generation. This is the concern and question of the author, concerning public attention to the discussion of the dimly lit shop? In finding answers to these conditions, it is done by studying and exploring these considerations by research. This study aims to describe the forms of public awareness of the dimly lit stalls against Islamic Counseling Guidance in Jorong Lubuk Gadang. This research is a field research, using qualitative descriptive methods that are methods that describe and describe events in accordance with the actual situation. The data source in this study is community leaders. Data collection techniques carried out through observation and interviews. Then the data is completed and analyzed. The results of the study found that (1) The form of mamak ninik's concern for the dimly lit stalls is to have empathy for the community and for the visitors, namely finding what is understood by the community, which is meant by the establishment of the dimly lit community stalls that are told fretically and is also often sought after . Another form of caring giving help is morale to the stall owner. Help is given by praying for the owner of the stall to be aware of his actions. The next form of concern is to behave prosocially towards the community. Prosocial behavior in mamak ninik is by inviting the community to work together to ask for the approval of the dimly lit shop to the invited party. (2) The form of concern of religious scholars to the dimly lit shop is to go to the location of the dimly lit shop to be discussed earlier to prevent the establishment of the dimly lit shop. (3) A clever form of caring for the dimly lit shop is to fight warmly against fellow community members, always kind and gentle towards the community, coming to this shop to reprimand the owner of the warung immediately to make an agreement and report to the person invited.